Survival and mortality from oral cancer by anatomical location. A narrative review. - Jorge Candia; Alejandra Fernández; Kim Kraemer (Universidad de Concepción., 2016)
Oral cancer is a global problem. It is the sixth most frequent cancer among all types of cancer and can affect different areas of the oral cavity. Survival rates are influenced by various factors, such as: histological type, tumor size, presence of regional and/or distance metastases, and the biological status of the patient. According to WHO, survival rate from oral cancer at 5 years is 53-56%. The objective of this review is to describe the survival and mortality rate from oral cancer by anatomical location at national and global scale. Globally, the survival rate for cancer located at the lips, tongue, floor of the mouth, palate, jaws, alveolar ridge and salivary glands ranges from 0% to 100%. However, Chile has not reported the survival rate for different anatomical locations. No information was found in relation to mortality rates for different anatomical locations in Chile and in the world. It is considered that oral cancer affecting the tongue, floor of the mouth, palate and alveolar ridge have the worst prognosis, and conversely, those affecting the lower lip have the best prognosis.